Legends of a Transylvanian Shrine to the Virgin Mary - Magyar, Zoltán (Ethnographica et Folkloristica Carpathica, 2021)
My paper presents a legend tradition related to a well-known Hungarian (Transylvanian) place of pilgrimage. Csíksomlyó (Miercurea–Ciuc/Sumuleu) – currently part of Romania ‒ has become a significant place of pilgrimage in the 20th century, similarly to Austria’s Mariazell, Spain’s Santiago de Compostela, the Orthodox Church’s Athos, or the main international shrines to the Virgin Mary (Lourdes, Fatima, Medjugorje). Around this famous pilgrimage place known from the 15th century a thematically rich legend circle has developed over the centuries, typical of Hungarian folklore, which abounds in historical and narrative traditions. At the centre of the group of legends stands the statue of the Virgin Mary, of gothic origin, the miraculous reputation of which is complemented by several historical legend themes (foundational traditions, wars, heroes and saints, crime and punishment and other legend motifs inspired by the sacred place). I highlight the most important historical perspectives, the chronological characteristics, the geographical distribution and, above all, the typological diversity of these legends. The legend circle of the shrine of Csíksomlyó in Romania is the totality of the related narrative traditions, that is to say, both the hundred-year-old miracle stories found in written form in different historical sources, and the recent folklore texts collected from oral tradition. Although the time and the circumstances of the records differ significantly, the aim of the narration and the topic of the legends are the same. The legends about the shrine – separated into the given thematic groups – are an organic part of the Catalogue of Hungarian Historical Legends.